Effect of initial sorting and amount of added fat on performance of growing-finishing pigs reared in a commercial facility - C W Hastad; Michael D Tokach; Robert D Goodband; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
Two studies were conducted to determine whether the amount of dietary energy fed to pigs of different weight categories influenced growth performance, market weight, and economic return in a commercial grow-finish facility. In Experiment 1, a total of 1,032 pigs with initial weight of 67.7 lb were individually weighed, fitted with electronic ear tags, and sorted into ten, 5-lb weight categories. Pigs were then allotted to pens lighter and heavier then the barn mean or to pens remixed to create a normal distribution around the mean. To complete the 2 × 3 factorial, pigs were fed corn-soybean meal diets, with or without 6% choice white grease. For the overall trial, there were no fat × weight-category interactions (P>0.15). Pigs fed 6% added fat tended (P<0.07) to have greater ADG (1.79 vs. 1.76 lb), but added fat did not affect (P>0.15) SD or CV of gain for the overall trial. For weight category, regardless of diet, heavy pigs grew faster (P<0.01, 1.83, 1.72, and 1.76 lb) than either the light or mixed pigs, respectively. In Experiment 2, 1,176 pigs with an initial weight of 77.4 lb were tagged and visually sorted into five weight categories. Pigs (28 per pen) were then allotted to pens lighter and heavier than the barn mean or remixed to create a normal distribution around the mean. To complete the 2 × 3 factorial, pigs were fed corn-soybean meal diets, with or without 6% choice white grease. For the overall trial, there were no fat × weight-category interactions (P>0.25). Pigs fed 6% added fat had greater (P<0.07) ADG, but there was no difference(P>0.61) in SD or CV for ADG during the overall study. For weight category, regardless of diet, heavy pigs grew faster (P<0.02, 1.96, 1.92, and 1.94 lb) than either the light or mixed pigs, respectively. Although no interactions existed for growth or carcass data, there was a fat × weight-category interaction (P<0.07) for the financial response of margin over feed cost (MOF). Heavy pigs in both studies had greater (P<0.01) MOF than either light or mixed pigs; when comparing 0 and 6% added fat within weight category, however, the increase in MOF was greater for light pigs fed added fat than for heavy pigs fed added fat. These studies indicate that adding 6% added fat does not increase variation within or across a population. Because adding fat to the diets of lightweight pigs improves their growth rate, dietary fat can be used selectively in the barn to increase the weight of the lightest 50% of the pigs.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Swine; Finishing pig; Dietary fat; Variation